The Influence of E-Performance on the Effectiveness of Personnel Information System Management in Educational Institutions in Muara Wahau - Hediati Mahardika; Dedy Hartanto; Rizki Gagah Perkoso; Supriadi Supriadi; Laili Komariyah; Yudo Dwiyono (Poltanesa, 2026)
This study aims to analyze the influence of E-Performance (E-Kinerja) implementation on the effectiveness of Personnel Information System (SIK) management in educational institutions across Muara Wahau District. The background of this research is driven by the growing demand for digital bureaucratic reform that emphasizes efficiency, transparency, and accountability in civil service performance management. The E-Performance system is expected to accelerate performance reporting, improve data accuracy, and support data-driven decision-making within an integrated personnel information framework. This study employs an associative quantitative approach using an explanatory survey method. The population consists of 120 employees, with a sample of 85 respondents selected through proportionate stratified random sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using validity testing, reliability testing, simple linear regression, coefficient of determination (R²), and t-test. The results show that all questionnaire items are valid (r > 0.30) and reliable (α > 0.70). The regression equation obtained is Y = 12.34 + 0.68X, with t-value = 9.48 > t-table = 1.99 and p = 0.000, indicating a positive and significant influence between E-Performance and SIK effectiveness. The R² value of 0.629 reveals that 63% of the variation in SIK effectiveness is explained by E-Performance implementation. These findings confirm that E-Performance contributes to enhancing efficiency, accuracy, and transparency in personnel management, emphasizing the need for continuous digital training and system integration improvement within educational institutions.